Relationships, resources, and political empowerment: community violence intervention strategies that contest the logics of policing and incarceration - Dawson, Mia Karisa; Ivey, Asia; Buggs, Shani (Frontiers in Public Health, 2023)
Community violence—defined as unsanctioned violence between unrelated individuals in public places—has devastating physical, psychological, and emotional consequences on individuals, families, and communities. Immense investments in policing and incarceration in the United States have neither prevented community violence nor systemically served those who have been impacted by it, instead often inflicting further harm. However, the logics that uphold policing and incarceration as suitable or preventative responses to community violence are deeply ingrained in societal discourse, limiting our ability to respond differently. In this perspective, we draw from interviews with leading voices in the field of outreach-based community violence intervention and prevention to consider alternative ways to address community violence. We begin by demonstrating that policing and incarceration are distinguished by practices of retribution, isolation, and counterinsurgency that are counterproductive to the prevention of community violence. Then, we identify alternative practices of outreach-based community violence intervention and prevention that include (1) fostering safety nets through relationships among individuals, families, and neighborhoods, (2) fighting poverty and increasing access to resources, and (3) building political capacity among organizations to transform the broader systems in which they are embedded. They also include accountability practices that are preventative and responsive to the needs of those who are harmed. We conclude that elevating the language, narratives, and values of outreach-based community violence intervention and prevention can transform our responses to violence, interrupt cycles of harm, and foster safer communities.